2002
DOI: 10.1046/j.1365-2141.2002.03872.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular histogenesis of plasmablastic lymphoma of the oral cavity

Abstract: Summary. Plasmablastic lymphoma (PBL) of the oral cavity is an aggressive B-cell lymphoma associated with human immunodeficiency virus infection. Although the lymphoma phenotype is consistent with late B-cell maturation, the molecular histogenesis of PBL is unknown. We investigated PBL of the oral cavity (n ¼ 12) for mutations of immunoglobulin variable heavy chain (IgV H ) and BCL-6 genes, which are acquired by B cells at the time of germinal centre (GC) transit, and for expression of BCL-6, MUM-1 and CD138, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 30 publications
3
53
1
Order By: Relevance
“…7 Previous reports have shown that plasmablastic lymphoma has a terminally differentiated B-cell or plasma cell immunophenotype, characterized by weak or absent expression of conventional B-cell markers, and strong expression of the post germinal center B-cell-and plasma cell-associated markers MUM1/IRF4 and CD138/syndecan-1. [1][2][3]8,9 This immunophenotype is similar to that reported for plasmablastic plasma cell myeloma. 1,8,10,11 In practice, the distinction between plasmablastic lymphoma and plasmablastic plasma cell myeloma frequently depends on clinical correlation.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…7 Previous reports have shown that plasmablastic lymphoma has a terminally differentiated B-cell or plasma cell immunophenotype, characterized by weak or absent expression of conventional B-cell markers, and strong expression of the post germinal center B-cell-and plasma cell-associated markers MUM1/IRF4 and CD138/syndecan-1. [1][2][3]8,9 This immunophenotype is similar to that reported for plasmablastic plasma cell myeloma. 1,8,10,11 In practice, the distinction between plasmablastic lymphoma and plasmablastic plasma cell myeloma frequently depends on clinical correlation.…”
supporting
confidence: 79%
“…In agreement with previous studies, all of the plasmablastic lymphoma cases in this study had a post-germinal center B-cell/plasma cell phenotype, expressing MUM1/IRF4 and CD138/syndecan-1, but negative for CD20. 3,[20][21][22] Furthermore, we observed that several markers that may be aberrantly expressed in plasma cell neoplasms, CD56, CD10 and CD4, were also expressed in most cases of plasmablastic lymphoma. CD56 and CD10, markers frequently expressed in plasma cell myeloma, [23][24][25] were positive in 5/9 and in 6/9 of the plasmablastic lymphoma cases in our series, respectively.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…PBL is strongly associated to EBV [1,4,6,10,20,29,30] and is not necessarily confined to head and neck area as once believed [1,10,16,[30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Gaidano et al investigated 12 cases of PBL of the oral cavity for somatic IgV H hypermutations and found 4 of 10 cases to be positive for this mutation while six cases displayed germline IgV H genes. Whereas all of their cases, regardless the IgV H mutational state were BCL-6 negative, indicating a lack of transit through the germinal center, all of the cases consistently revealed strong expression of CD138 and MUM-1, markers of preterminal plasma-cell differentiation [17]. From these studies the authors concluded that the IgV H hypermutated subset carried the molecular clues of germinal center transit and conceivably originated from a post-germinal center B-cell, while the IgV H unmutated group appeared to originate from a naïve B-cell that had undergone post-germinal differentiation independent of germinal center transit.…”
Section: Discussionmentioning
confidence: 96%